Competitive Advantage Analysis of Mud Crab (Scylla serrata) Commodity Value Chain in Pallime Village and Pusungnge Village, Cenrana District, Bone Regency - Sitti Normawati; Syainullah Wahana; Rini Rini; Andi Besse Dahliana; Yusnan Suyuti DM; Mirna Mirna; Muhammad Nur; Muhammad Said (Politeknik Negeri Sambas, 2025)
Pallime and Pusungnge villages are key production centers for mud crabs, serving both local consumption and export markets. This study aims to assess the competitive advantage of mud crab commodities, focusing on productivity, quality, continuity, and marketable pricing. The research was conducted from May to July 2025 in Pallime and Pusungnge villages. A qualitative method was employed, utilizing both primary and secondary data collection techniques. The results indicate that in the mud crab value chain of Pallime and Pusungnge, four main actors are involved: fishers, farmers, and collectors. Female crabs consistently fetch higher prices than male crabs. The price difference between farmers and collectors to consumers indicates that collectors obtain the highest profit margins within the mud crab distribution chain. Four types of marketing channels were identified: fishers selling directly to consumers, farmers selling directly to consumers, farmers selling to collectors, and collectors selling to traders before the products reach end consumers. A subsequent SWOT analysis identified key strengths, such as supportive mangrove ecosystems; weaknesses, including limited access to modern technology; opportunities, such as domestic and export market demand; and threats, such as environmental degradation. By leveraging strengths and opportunities while addressing weaknesses and threats, the mud crab value chain can be significantly enhanced.